FACTORS AFFECTING SINGLE FATHER'S QUALITY OF LIFE DURING THE COVID-19 PANDEMIC - Hamaedi, Hana Fauziah; Rizkillah, Risda (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2024)
Single-father families are vulnerable to economic problems during the Covid-19 pandemic. This study aims to analyze factors that influence the quality of life of single fathers during the Covid-19 pandemic. This research uses quantitative research methods with a cross-sectional study design involving 60 single fathers who were selected using purposive sampling with the criteria of 1) being domiciled in Leuwiliang District, 2) living with dependent children in the same house, and 3) having separated from their partner due to divorce. Life or death divorced. The results of the study found that almost half of single fathers had a moderate quality of life and objective and subjective economic pressure, and most single fathers had low coping strategies. The correlation test showed that objective and subjective economic pressure was negatively related to quality of life. In contrast, per capita income and coping strategies were positively related to quality of life. The regression test shows that subjective economic pressure hurts quality of life, while coping strategies positively impact quality of life.